Scientific and pedagogical foundations of developing the skills of listening to national music in higher education system - Elmurod Maxmudjonovich Tajiboyev (Science and Education, 2026)
This article analyzes the essence and significance of developing the skills of listening to national music in the higher education system. It discusses how national music contributes to the spiritual and aesthetic development of students, the formation of their aesthetic taste and cultural literacy, as well as the development of their creative activity and independent thinking skills. The study highlights the educational role of national music, the effectiveness of interactive approaches, and the use of information and communication technologies in modern educational processes. Additionally, the article emphasizes that listening to national music helps cultivate patriotism, respect for cultural heritage, and awareness of national identity among students. Keyword: snational music, listening skills, aesthetic culture, higher education, spiritual education, creative activity, interactive approach, information and communication technologies